Digital Literacy as Ethical Competence: Research Integrity in AI-Mediated Academic Work among LIS Students in Nigeria - Aderinola Ololade Dunmade (IQRO: Journal of Islamic Education, 2026)
This study explores how digital literacy shapes research integrity among final-year Library and Information Science students at the University of Ilorin, Nigeria, within AI-mediated academic environments. Using a qualitative phenomenological approach, data were collected from thirty participants through interviews and focus groups and analysed thematically to capture students’ experiences of digital research and ethical decision making. The findings show that although students display strong ethical awareness linked to their professional identity, this does not always translate into practice. Digital competence supports source evaluation and reference management, but also enables uncritical copying, use of rewriting tools, and uncertain engagement with artificial intelligence, especially under academic pressure. Behaviour is further influenced by inconsistent supervision, unclear institutional guidance, and peer norms. The study reframes digital literacy as an ethical competence rather than a purely technical skill, showing that its role in research integrity depends on intention and context. It contributes evidence from an underexplored African setting and highlights the need for clearer, discipline-sensitive policies on AI use, alongside stronger supervision and integrity education.